2019
DOI: 10.1016/j.psep.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

A technoeconomic assessment of microalgal culture technology implementation for combined wastewater treatment and CO2 mitigation in the Arabian Gulf

Abstract: A technoeconomic assessment (TEA) has been conducted of the feasibility of large-scale application of microalgal culture technology (MCT) to the combined mitigation of CO2 emissions from flue gases and nutrient discharges from wastewater in the Arabian Gulf. The assessment has incorporated the selection of the algal species and MCT technologies, the extent of nutrient removal, and the biomass/biofuel production rate. The cost benefit of the abatement of pollutants (in the form of CO2 and nutrient discharges) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…The use of traditional fossil fuels (eg, oil and coal), for energy production, causes the emissions of CO 2 and other greenhouse gases (GHGs) 6 and contribute to the global warming (GW). 7,8 These are major environmental challenges that affect public health and the wellbeing of individuals. 3,[9][10][11][12] Therefore, the attention of the scientific community was diverted toward sustainable, renewable, and clean energy resources that can replace existing internal combustion engines [13][14][15][16][17] and mitigate the emissions of GHGs.…”
Section: Introductionmentioning
confidence: 99%
“…The use of traditional fossil fuels (eg, oil and coal), for energy production, causes the emissions of CO 2 and other greenhouse gases (GHGs) 6 and contribute to the global warming (GW). 7,8 These are major environmental challenges that affect public health and the wellbeing of individuals. 3,[9][10][11][12] Therefore, the attention of the scientific community was diverted toward sustainable, renewable, and clean energy resources that can replace existing internal combustion engines [13][14][15][16][17] and mitigate the emissions of GHGs.…”
Section: Introductionmentioning
confidence: 99%
“…Companies like HydroMentia, OneWater , and Gross‐Wen Technologies all commercialize wastewater treatment solutions based on immobilized microalgae (or a combination microalgae/bacteria) with various configurations (Wollmann et al, 2019). However, a huge number of different factors are affecting microalgal growth and the removal of nutrients from wastewater (Al Ketife et al, 2019).…”
Section: Wastewater Reclamation By Microalgaementioning
confidence: 99%
“…They found that in this context the break-even selling price is 0.49 € per kg algal biomass, equating to 0.81 € per L for the extracted biocrude (adjusted value), and they reported the high sensitivity to the algal growth rate. [151] Thus, biomass productivity is seen as the major factor impacting the unit production cost. As suggested by Meylan et al, [115] the algae pathway can also be considered within the framework of an integrated biorefinery to become economically more viable.…”
Section: Co 2 To Biological Algae Cultivation and Enzymatic Conversionmentioning
confidence: 99%
“…Nevertheless, they indicated that the economic viability of large‐scale algal biofuel production depends on a significant decrease in equipment costs (e.g., photobioreactors) and/or public policy intervention, and is limited by the long‐term availability of phosphorus. [ 150 ] More recently, Ketife et al [ 151 ] conducted a TEA to evaluate the feasibility of a microalgal culture technology large‐scale application, that combined CO 2 flue‐gas bio fixation and wastewater treatment in the Arabian Gulf. They found that in this context the break‐even selling price is 0.49 € per kg algal biomass, equating to 0.81 € per L for the extracted biocrude (adjusted value), and they reported the high sensitivity to the algal growth rate.…”
Section: Techno‐economic Feasibility Sustainability and Social Percmentioning
confidence: 99%